PEMAKNAAN KRITERIA KESAHIHAHAN HADIS MUḤAMMAD NÂṢIR AL-DÎN AL-ALBÂNÎ DAN IMPLEMENTASINYA DALAM PENILAIAN HADIS - Farida, Umma (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
This article aims to examine the theoretical framework of Muḥammad Nâṣir al-Dîn al-Albânî on ḥadîth. It has been known that sometimes al-Albânî explicitly put some ḥadîths into unsound classification, whereas some major ḥadîth scholars put the ḥadîth in valid and authentic condition. Through studying his book entitled Silsilat al-Aḥâdîth al-Ṣaḥîḥah and some other books, this articel finds that although in some cases his conclusion is quite different from other ḥadîth scholars, he is still standing on the previous principles to determine the validity of ḥadîth such like: chain continuity (ittiṣâl al-sanad), fair narrators (‘âdil) and having good intellectuality (ḍâbiṭ), safe from berration (shudhûdh) and trouble (‘illat), but at some points, he has made his own differentiation in defining those principals. Besides, al-Albânî has also given special attention to the validity of matn (the content of ḥadîth), that the matn should not be contrary with the Qur’ân, sunnah Ṣaḥîḥah (the valid tradition), logical reasoning, historical facts, sciences, and the practice of previous piety (salaf al-Ṣâliḥ).